The Effects of Cannabis on Male Fertility: A Literature Review - Kusibab, Karolina; Sikora, Gabriela; Woźniak, Martyna; Kutnik, Karolina; Koguc, Karolina; Czechowski, Michał; Skórska, Gabriela; Słomianny, Marcela; Kolada, Karolina; Sajda, Małgorzata (Quality in Sport, 2025)
Background: Cannabis is a commonly used drug, both recreationally and in medicine, that has a big impact on endocannabinoid system responsible for human reproductive functions. Aim: The review of current literature on the effects that cannabis has on male reproductive system. Methodology: A review was conducted using PubMed, Google Scholar, and ResearchGate. Search terms included: cannabis, marijuana, male fertility, cannabis use disorder, endocannabinoid system. Studies published between 2020-2025 were reviewed. Results: Chronic marijuana use can potentially lead to fertility problems in male population, such as decreased sperm motility, DNA integrity or compromised capacitation, leading to troubles with egg fertilization and conception, however, the research is not conclusive. Conclusions: Men planning reproduction should consider abstinence from both THC and CBD, because of their potential impact on male fertility, but further studies in this area should be considered.